TikTok @Tvtani as a Communication Media for the Ministry of Agriculture in Improving Engagement - Zalnovera Zalnovera; Rufki Ade Vinanda (Universitas Pendidikan Nasional, 2025)
TikTok has currently emerged as a popular social media platform with a rapidly growing user base. This growth presents significant opportunities for various parties, including institutions and organizations, to utilize TikTok as a strategic communication medium. Government agencies are no exception, leveraging TikTok for public communication. The Indonesian Ministry of Agriculture has utilized various social media platforms, including TikTok, to disseminate agricultural information through an account named @TVTani. Consequently, this study focuses on identifying the strategies employed by the @TVTani TikTok account in utilizing the platform to enhance engagement. This research aims to analyze the strategies implemented by TV Tani in leveraging TikTok to increase audience engagement, particularly within the agricultural sector. A qualitative case study method involving in-depth interviews was employed. The informants for this study consisted of four individuals holding the positions of Editor-in-Chief, Social Media Specialist, Video Editor, and Camera Person (Campers). The findings reveal that the @TVTani TikTok account has successfully transformed into an effective strategic communication medium. Overall, @TVTani's success in increasing engagement lies in the synchronization of trend research, visual creativity, and rigorous quality control, while continuously adapting to the ever-changing dynamics of social media user behavior. This study contributes to enriching the literature on how government agencies implement engagement strategies, specifically in the agricultural sector. It is expected that this research will serve as a guide for government institutions in optimizing social media content management.